The PhenX Toolkit: measures for tobacco regulatory research. (28th January 2020) - Swan, Gary E; Hendershot, Tabitha P; Hamilton, Carol M; van Bemmel, Dana M; Wanke, Kay L
Abstract : The use of standard measures and common data elements in the conduct of tobacco regulatory research (TRR) will improve data comparability and facilitate cross-study analyses and replication of findings to inform the regulatory decisions and actions of the US Food and Drug Administration (FDA) Center for Tobacco Products (CTP). This overview paper introduces the PhenX (consensus measures for Phenotypes and eXposures) initiative to identify common measures and common data elements for use in TRR which have been disseminated in the PhenX Toolkit (https://www.phenxtoolkit.org/ ). It describes the work of the scientific panel that provided guidance to the project and the TRR Core Collection of measures recommended for use by investigators conducting human-subject tobacco regulatory or related tobacco control research. The use of PhenX TRR measures will promote collaborative research and facilitate data interoperability and validation of outcome assessments to inform the FDA CTP's regulatory activities.